2005
DOI: 10.1007/s10620-005-2857-5
|View full text |Cite
|
Sign up to set email alerts
|

Diallyl Trisulfide Inhibits Tumor Necrosis Factor-α Expression in Inflammed Mucosa of Ulcerative Colitis

Abstract: The present study aimed to investigate the effect of diallyl trisulfide (DATS) on tumor necrosis factor (TNF)-alpha expression in inflammed mucosa of ulcerative colitis and its possible mechanism. Colonic biopsies from ulcerative colitis were treated with 0, 1, 5, and 10 microM DATS for 24 hr. Lactate dehydrogenase (LDH) activities and concentrations of TNF-alpha in supernatants were measured. mRNA expressions of TNF-alpha in biopsies were analyzed by RT-PCR. The expression of NF-kappaB P65 in tissues was stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 21 publications
2
10
0
1
Order By: Relevance
“…Previously, a garlic-derived substance that releases H 2 S (allyl trisulfide) 37 was shown to suppress TNF-␣ expression and NF-B activation in colonic biopsy samples from ulcerative colitis patients. 38 We also observed that an inhibitor of H 2 S synthesis markedly down-regulated colonic COX-2 activity, and this was accompanied by reduced colonic prostaglandin E 2 synthesis and induction of inflammation in the tissue. COX-2 is a source of several antiinflammatory eicosanoids and plays a crucial role in the resolution of inflammation in many tissues, 39 -41 including the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 54%
“…Previously, a garlic-derived substance that releases H 2 S (allyl trisulfide) 37 was shown to suppress TNF-␣ expression and NF-B activation in colonic biopsy samples from ulcerative colitis patients. 38 We also observed that an inhibitor of H 2 S synthesis markedly down-regulated colonic COX-2 activity, and this was accompanied by reduced colonic prostaglandin E 2 synthesis and induction of inflammation in the tissue. COX-2 is a source of several antiinflammatory eicosanoids and plays a crucial role in the resolution of inflammation in many tissues, 39 -41 including the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 54%
“…Many researches are pursuing potent new drugs for IBD management. To date, a lot of papers have reported that some components of vegetables and herbs can inhibit the inflammatory response of IBD or experimental colitis [4][5][6], and show new potential therapeutics for IBD in future.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is substantial evidence that H 2 S is produced throughout the GI tract and it participates in many physiological functions in addition to promoting mucosal integrity, reducing mucosal inflammation and accelerating healing of ulcers [28] – [30] , [34] , [38] . Accleration of ulcer healing is most likely related to the ability of H 2 S to promote angiogenesis [30] , [39] , while prevention of tissue injury may be related to the ability of H 2 S to maintain mucosal blood flow [29] , [38] , stimulate bicarbonate secretion [40] , [41] , stimulate mucus secretion [42] , inhibit leukocyte adherence to the vascular endothelium [43] , scavenge free radicals [44] , promote resolution of inflammation by increasing neutrophil apoptosis [45] and differentiation of macrophages to the M2 phenotype [46] , and suppress production of pro-inflammatory cytokines (including IL-1, IL-2, IL-8 and TNFα) [47] [50] , while maintaining or increasing production of IL-10 [47] [50] . Suppression of IL-8 production in keratinocytes by H 2 S has been reported to be a consequence of diminished IL-17 production, as IL-17 can induce IL-8 production [51] , [52] .…”
Section: Discussionmentioning
confidence: 99%